2021
DOI: 10.1093/jacamr/dlab174
|View full text |Cite
|
Sign up to set email alerts
|

Cefiderocol treatment for carbapenem-resistant Acinetobacter baumannii infection in the ICU during the COVID-19 pandemic: a multicentre cohort study

Abstract: Objectives To analyse the impact of cefiderocol use on outcome in patients admitted to the ICU for severe COVID-19 and further diagnosed with carbapenem-resistant Acinetobacter baumannii (CR-Ab) infection. Methods Retrospective multicentre observational study was performed at four Italian hospitals, from January 2020 to April 2021. Adult patients admitted to ICU for severe COVID-19 and further diagnosed with CR-Ab infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 20 publications
6
60
1
2
Order By: Relevance
“…Consistent results were reported by a comparative study on COVID-19 patients, which compared cefiderocol to BAT in patients with bacteremia and nosocomial pneumonia due to A. baumannii [ 27 ]; 107 patients were enrolled: 42 treated with cefiderocol and 65 with other therapies (among others colistin). No differences in mortality at day 28 were reported (55% vs 58%, p = 0.706).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Consistent results were reported by a comparative study on COVID-19 patients, which compared cefiderocol to BAT in patients with bacteremia and nosocomial pneumonia due to A. baumannii [ 27 ]; 107 patients were enrolled: 42 treated with cefiderocol and 65 with other therapies (among others colistin). No differences in mortality at day 28 were reported (55% vs 58%, p = 0.706).…”
Section: Resultssupporting
confidence: 59%
“…Due to its recent approval and the exiguity of published studies, the place in therapy of cefiderocol has to be still defined, thus conveying its strength in guidelines [ 7 , 9 ]. Anyways, even more evidence is coming to light among literature, since recent clinical studies have demonstrated the important role that cefiderocol can play in the eradication of infections caused by Gram-negative MDR pathogens [ 17 , 27 – 29 , 37 ]. Beta lactamase antibiotics, as carbapenems, are still considered the best available therapy against Gram-negative extended-spectrum β-lactamase (ESBL)-producing pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…All-cause 28-day mortality rate was 57%, without differences between groups ( P = 0.70). In this study, cefiderocol was associated with a non-significant lower mortality risk ( P = 0.10) ( Pascale et al., 2021 ).…”
Section: New Approved Therapeuticmentioning
confidence: 67%
“…Our post hoc analysis data are complemented by efficacy findings for cefiderocol in real-life cases of difficult-to-treat severe gram-negative infections. Microbiological clearance from repeat blood cultures was seen in around 67% of a total of 60 patients with BSI due mainly to CR or XDR A. baumannii and difficult-to-treat resistant P. aeruginosa [34][35][36][37][38][39][40][41][42]. A more complete picture of the real-world efficacy of cefiderocol in gram-negative BSI patients will be provided by the ongoing Phase 2 GAMECHANGER study, an open-label, prospective, randomised, controlled, non-inferiority trial, comparing cefiderocol and standard of care in the treatment of healthcare-associated or hospital-acquired BSI (NCT03869437; [43]).…”
Section: Discussionmentioning
confidence: 99%